Kelayakan Finansial Pembangunan Kawasan Agribisnis Nilam PT Agro Usaha Mandiri di Kabupaten Aceh Jaya - Idal Bahri; Yunida Pangastuti (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2021)
The patchouli commodity (Pogostemon Cablin Benth.) Is a plant that produces essential oils with very good economic value in the international market, considering that only a few countries produce this commodity, including Indonesia. Thus the development of this commodity is a strategic step in developing patchouli agribusiness in Indonesia.PT. Agro Usaha Mandiri plans to develop a patchouli agribusiness area in Pasie Raya District, Aceh Jaya Regency, which covers an area of 3,000 ha. The company uses processing technology (distillation) that is more efficient and of high quality in order to be competitive and more efficient and more economical than the existing conventional systems.This research discusses the financial feasibility study for investment carried out by PT. Agro Usaha Mandiri. The company's investment is in the form of patchouli agribusiness development. The method used is the Investment Criteria. Investment criteria are calculating the value of Net Present Value, Internal Rate of Return, Payback Period, and Benefit Cost Ratio. From the analysis, it is found that the investment made to run a business is declared feasible to be implemented with an NPV value greater than 1 and an IRR greater than the interest rate used (12%) with a payback period (PP) that is faster than the investment age (10 year) and the value of the B / C Ratio is greater than 1.